Proses Berpikir Siswa dalam Menyelesaikan Masalah Bilangan Berpangkat dan Bentuk Akar Berdasarkan Teori Pemrosesan Informasi - Khotimah, Husnul; Sa’dijah, Cholis; Rofiki, Imam; Latifah, Eka Ratna Anjanuarti (MATHEdunesa, 2024)
Information processing theory is a theory that can explain students' thinking processes in problem-solving. Effective problem-solving requires a good thinking process. Thus, exploring students' thinking processes will help in understanding the causes of students' mistakes so that they can be prevented and enhance students' problem-solving eventually. In line with that, this research aims to analyze students' thinking processes in solving powers and root forms problem (in mathematics) based on information processing theory. This case method research with a qualitative approach was carried out at SMP Laboratorium Universitas Negeri Malang (UM) involving two subjects. The findings show that for both student who answer correctly and student who answer incorrectly, the thinking process begins with the entry of stimuli into sensory memory which is then selected through selective attention to obtain perception. The information is then passed to short-term memory. The difference in their thinking processes lies in the retrieval process. The student who answered correctly succeeded in solving the problem correctly even though he experienced a forgotten lost while the student who answered incorrectly experienced misperceptions caused by a forgotten lost which resulted in the strategy execution and the final answer being incorrect.